The Cholevidae (Coleoptera) of Sardinia - Casale, Achille; Grafitti, Giuseppe; Latella, Leonardo (Zootaxa, 2009)
We present a synthesis of the knowledge on the cholevid fauna of Sardinia, with an annotated checklist and an updated list of both published and unpublished collecting localities. The Cholevidae (Coleoptera, Staphylinoidea) are a group of small to medium-sized beetles, most of which are saprophagous; a significant percentage of Cholevidae are cave-dwellers, and some are highly specialized troglobitic elements. In Sardinia, twenty-five species have been recorded so far. More than half of them are endemic to the island, while some are sub-endemic (i.e. present also in Corsica or in Sicily and/or the Balearic Islands); nine species, belonging to the genera Ovobathysciola and Patriziella, are specialized hypogean elements. Four more species, belonging to the genus Bathysciola, are soil-inhabiting or cave-dwellers. The authors stress the high biogeographic and biospeleological interest of Sardinian cholevids. In particular, the colonization processes appear to be in good agreement with the current hypotheses about the origin and composition of the existing fauna of Sardinia. The hypogean species of the genera Ovobathysciola, Patriziella and species of Speonomus of the subgenus Batinoscelis are currently accepted as being related to the Baetic and Pyrenean lineages of Anillochlamys and Speonomus, respectively; therefore, they should belong to the most ancient stock of elements, originated during the Miocene drift of the Corso-Sardinian massif in the western Mediterranean. Some other endemic or sub-endemic taxa, with W-Mediterranean affinities, are probably derived from more recent colonizers as a consequence of the several connection/isolation phases which existed between Sardinia, Corsica, and other Mediterranean areas during the late Miocene (Messinian) salinity crisis, and during the Plio-Pleistocene ice-phase-related strong variations in the sea level. Finally, some widespread taxa, all epigean and winged, reached the island in more recent times, through active and passive dispersal.